Penulisan Laporan Penelitian Pendidikan (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Writing an educational research report is essential to disseminate research results and apply scientific findings in educational practice. A good report must be written systematically, structured, and in accordance with academic standards. This study uses literature study to review guidelines and examples of educational research reports. The results show that reports generally consist of a title, introduction, literature review, methods, results and discussion, and conclusions, appendices, and bibliography. Each section has a different but interrelated function to convey the research results completely. This study emphasizes the importance of attention to the writing structure so that the report is effective and meets academic standards. With the right understanding, research reports can make a significant contribution to the development of education.